2007
DOI: 10.1037/0022-006x.75.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Site matters: Multisite randomized trial of motivational enhancement therapy in community drug abuse clinics.

Abstract: The effectiveness of motivational enhancement therapy (MET) in comparison with counseling as usual (CAU) for increasing retention and reducing substance use was evaluated in a multisite randomized clinical trial. Participants were 461 outpatients treated by 31 therapists within 1 of 5 outpatient substance abuse programs. There were no retention differences between the 2 brief intervention conditions. Although both 3-session interventions resulted in reductions in substance use during the 4-week therapy phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
235
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(244 citation statements)
references
References 40 publications
6
235
3
Order By: Relevance
“…Given this pattern of results, it is difficult to speculate about what site characteristics, if any, might have contributed to the results observed. The finding of site effects is consistent with a CTN multisite study of MET, which also found evidence of site effects (Ball et al, 2007). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Given this pattern of results, it is difficult to speculate about what site characteristics, if any, might have contributed to the results observed. The finding of site effects is consistent with a CTN multisite study of MET, which also found evidence of site effects (Ball et al, 2007). …”
Section: Discussionsupporting
confidence: 80%
“…The failure to find an effect on substance use is inconsistent with the findings from a pilot study with pregnant alcohol drinkers which found that a 1 hour MI session, compared to letters informing participants of the risk of alcohol use during pregnancy, significantly lowered self-reported levels of intoxication in the subgroup of women who were using alcohol most heavily at baseline (Handmaker et al, 1999). There is a growing literature to suggest that the benefits of MET for primary drug abusers in substance abuse treatment might be more inconsistently observed compared to the benefits of MET for primary alcohol abusers (Ball et al, 2007). While the Handmaker et al (1999) study included all alcohol users, the present trial included only 21 participants (i.e., 10.5% of the study sample) who reported alcohol as the primary drug of choice; this difference in the two study samples could account for the differences in the study findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we provide a description of the therapeutic strategies and techniques used by clinicians delivering the TAU comparison condition during the early phase of treatment within nine community programs participating in two multisite randomized effectiveness trials in the NIDA Clinical Trials Network (CTN; Ball et al, 2007;Carroll et al, 2006). One protocol incorporated motivational interviewing (MI; Miller & Rollnick, 2002) into a one-session standard intake assessment (Carroll et al, 2006), henceforth referred to as motivational interviewing assessment (MIA).…”
Section: Introductionmentioning
confidence: 99%
“…One protocol incorporated motivational interviewing (MI; Miller & Rollnick, 2002) into a one-session standard intake assessment (Carroll et al, 2006), henceforth referred to as motivational interviewing assessment (MIA). The other protocol (Ball et al, 2007) examined the effectiveness of a three-session adaptation of the Motivational Enhancement Therapy manual used in Project MATCH (Miller, Zweben, DiClemente, & Rychtarik, 1992), henceforth referred to as MET. In both protocols, the effectiveness of MIA/MET was compared with outpatient individual TAU sessions that were equal in length and format.…”
Section: Introductionmentioning
confidence: 99%
“…One example is presented here in full. Martino et al (2008) evaluated community outpatient therapists' use of MET in a multi-site randomized effectiveness trial comparing three sessions of MET to counseling as usual (CAU) (Ball et al 2007). MET therapists and their supervisors were trained in 16-h intensive workshops; therapists completed audiotaped practice cases and received feedback until they achieved minimum certification standards.…”
Section: Observer-rated Adherence and Competencementioning
confidence: 99%